Corporate Governance Nexus with Human Values Towards Holistic Growth of Industry - V.J.K.Kishor Sonti; Mily Velayudhan T.K (AG Volumes, 2021)
Human component is the important resource of any Industry. Human Centric Development is always promising and prosperous. Corporate Governance is linked to management of human resources; availability of affective manpower is the biggest requirement of industry. The real challenge is in fetching and recruiting technically efficient and ethically sound manpower. If not, an incubation system or training centre must be in the Industry or associated firm for ensuring the quality and ethical man power. In this Chapter of the book, a clear emphasis was laid down on the positive aspects of human values in the holistic growth of the industry and ease in corporate governance. Trust, Confidence, Loyalty, Courage, Concern, Dedication and Integrity are some of the values in employees those make an organization healthier. Human resource policies of Corporate shall support employees in affective work-life balance management. The work-life conflict occurs mostly in working women, so dedicated policies or relevant framework shall be one of the crucial components in corporate governance. Research gaps, feasible solutions and means of mitigating challenges in corporate work environment are discussed in this chapter.